Pengaruh Harga dan Kualitas Produk Fashion terhadap Minat Beli Generasi Z di Tokopedia (Studi pada Mahasiswa di Tawangmangu) - Asri Rambu Lemba; Irwan Christanto Edy (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of price and product quality of fashion products on the purchase intention of Generation Z on the Tokopedia e-commerce platform, with a focus on students in Tawangmangu. This research employs a quantitative approach using purposive sampling, with a total sample of 100 respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS. The results indicate that price and product quality influence purchase intention, both partially and simultaneously. Price becomes a primary consideration for students due to budget constraints, while product quality influences consumer trust in online purchasing. These findings suggest that the alignment between price and product quality can enhance the purchase intention of Generation Z toward fashion products in e-commerce.